2020
DOI: 10.3233/jid180012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Design Representations on Creativity of Design Outcomes

Abstract: Designers usually spend non-negligible efforts in performing comprehensive design space explorations, but important information exchanged in conceptual design sessions is often lost, even about the rationale behind preferred solutions. As a part of a broader investigation concerning the impact of knowledge coming from previously performed design tasks, this paper describes an experiment aimed at assessing the impact on the design outcomes of two representations used to share existing design information. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The design creativity metric proposed by Shah et al (2000) was adopted to assess the results of the design experiment. This method is widely used in estimating the effectiveness of design methods (Cascini et al, 2018;Nelson et al, 2009;Wilson et al, 2010;Kim et al, 2014;Vandevenne et al, 2016). This approach relies on four dimensions to assess the ideas generated: quantity, quality, novelty and variety.…”
Section: Test Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design creativity metric proposed by Shah et al (2000) was adopted to assess the results of the design experiment. This method is widely used in estimating the effectiveness of design methods (Cascini et al, 2018;Nelson et al, 2009;Wilson et al, 2010;Kim et al, 2014;Vandevenne et al, 2016). This approach relies on four dimensions to assess the ideas generated: quantity, quality, novelty and variety.…”
Section: Test Evaluation Metricsmentioning
confidence: 99%
“…Our investigation focused on the methods relying on approaches based on Function-Based (FB) models of biological systems, since they constitute the great majority of the 43 "tools" identified by Wanieck et al (2016). Furthermore, it is well known that the efficacy of systematic conceptual design methods is strongly affected by the design representation adopted, as confirmed by Cascini et al (2018) among others. Therefore, in order to shed some light on these aspects, the overall purpose of this project was to study how BID design representations affect the actual ability of young engineers to generate design solutions inspired by Mother Nature.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive mechanisms behind creativity are extremely complex and still a debated topic, but it is widely acknowledged that design fixation (the counterproductive and often involuntary adherence to specific solutions or rationales) [28][29][30][31] is one of the main obstacles that hinder the generation of novel and original ideas. The literature offers many hints for overcoming design fixation, or in general for supporting creativity (e.g., [32][33][34]), where the type of representation of creative stimuli often plays a key role [35][36][37]. Indeed, it has been observed that providing examples could somehow support creativity, but the form in which such examples are provided may influence design outcomes [35].…”
Section: Creativity In Engineering Designmentioning
confidence: 99%
“…The selection of the type of representation to be inserted into the rows follows specific criteria. Indeed, it has been demonstrated in the literature that the way in which stimuli (in this case, the representations of the structural solution variants) are represented can affect the creativity of the design outcomes (e.g., [34,35,37]). However, while it seems that there is no difference between sketches and more detailed representations (e.g., photographs and CAD models) in terms of the novelty of the generated ideas, it seems that CAD models allow designers to obtain ideas characterized by higher quality [35].…”
Section: The Chart Of Structural Solution Alternativesmentioning
confidence: 99%
See 1 more Smart Citation